Language Style Analysis as Found in Come The Morning Movie A Sociolinguistics Study - Dewi Sartika Sitompul; Sondang Manik; Rony Arahta Sembiring (Institut Agama Islam Negeri Palopo, 2024)
The purpose of this study is to find a variety of language styles and the most dominant style of language in the film entitled Come the Morning by Billy Graham. This research used keraf theory, which has fourteen language styles: parable style, metaphor style, personification style, antithesis style, hyperbole style, climax style, sitir style, allusion style, erotic style, assonance style, chiasmus style, epizeukis style, epistropha style, and anaphora style. This study is a qualitative research with the descriptive design and in this study the writer found 122 data that has been classified into fourteen language styles.there are parable style 10%, metaphor style 1%, personification style 13%, antithesis style 3%, hyperbole style 4%, climax style 13%, sitir style 11%, allusion style 1%, erotic style 10%, assonance style 25%, chiasmus style, epizeukis style 3%, epistropha style 1%, and anaphora style 5%. Based on the research the most dominant types of movie come the morning by billy graham is Assonance (25%). In the movie Come the Morning, it is more inclined to use sentences or words that express a message or feeling experienced by the speaker in an imaginative or classic way.Â